The Analysis of Exclusive Breastfeeding Towards the Stunting Cases - Khafifa Luthfia; Rahajeng Siti Nur Rahmawati; Eny Sendra; Susanti Pratamaningtyas (Journal of Ners and Midwifery, 2023)
Stunting is a condition in which a child experiences developmental delays so that their height does not match their age, due to health problems during pregnancy, illness during infancy, and long-term lack of nutrition. One of the reasons for stunting is eating unbalanced, including exclusive breastfeeding as a baby. The impact of stunting besides growth, also causes minor illnesses, impaired brain development and intelligence, in the long term it can cause decreased mental capacity, decreased immune system so that it becomes weak easily, obesity, diabetes, stroke, heart and blood vessel disease, and old age disability. The aim of this study was to analyze the history of exclusive breastfeeding for the incidence of stunting. The research design was a quantitative correlation retrospective cohort approach, a population of 100 people with a sample of 50 people using the technique of simple random sampling. The study used Microtoice to measure the child's height was confirmed in table Z-Score and interview sheets for exclusive breastfeeding data. Analysis using Fisher Exact showed that the calculated P value (0.00) < error rate (0.1) had a relationship between a history of exclusive breastfeeding and the incidence of stunting. Based on this research, further information was needed on how to prevent stunting regarding the importance of clean and healthy life, especially for family members who smoke, because smoking had a negative impact on stunted toddler growth hormones